How Schools Affect Student Well-Being: A Cross-Cultural Approach in 35 OECD Countries - Govorova, Elena; Benítez, Isabel; Muñiz, José (Frontiers in Psychology, 2020)
A common approach for measuring the effectiveness of an education system or a school is the estimation of the impact that school interventions have on students’ academic performance. However, the latest trends aim to extend the focus beyond students’ acquisition of knowledge and skills, and to consider aspects such as well-being in the academic context. For this reason, the 2015 edition of the international assessment system PISA incorporated a new tool aimed at evaluating the socio-affective variables related to the well-being of students. It is based on a definition focused on the five dimensions proposed in PISA theoretical framework: cognitive, psychological, social, physical and material. The main purpose of this study is to identify the well-being components that significantly affect student academic performance and to estimate the magnitude of school effects on the well-being of students in OECD countries, the school effect being understood as the ability of schools to increase subjective student well-being. To achieve this goal, we analyzed the responses of 234,000 students from thirty-five OECD countries to PISA 2015 questionnaires. Specifically, we considered non-cognitive variables in the questionnaires and student performance in science. The results indicated that the cognitive well-being dimension, composed of enjoyment of science, self-efficacy and instrumental motivation, as well as the test anxiety all had a consistent relationship with student performance across countries. In addition, the school effect, estimated through a two-level hierarchical linear model, in terms of student well-being was systematically low. While the school effect accounted for approximately 25% of the variance in the results for the cognitive dimension, only 5-9% of variance in well-being indicators was attributable to it. This suggests that the influence of school on student welfare is weak, and the effect is similar across countries. The present study contributes to the general discussion currently underway about the definition of well-being and the connection between well-being and achievement. The results highlighted two complementary concerns: there is a clear need to promote socio-emotional education in schools, and it is important to develop a rigorous framework for well-being assessment. The implications of the results and proposals for future studies are discussed.